TRANSFORMASI EKONOMI LOKAL MELALUI BRANDING "KOPI KEBON WINDUAJI" - Ari Dwi Nurasih; Slamet Sulistiadi (Migunani Nusantara: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aims to enhance the entrepreneurial skills and capacities of Pokdarwis (Tourism Awareness Group) members in Winduaji Village through the development of a local coffee product, Kopi Kebon Winduaji. The implementation method includes potential and market surveys, training in production, packaging, marketing, licensing, and entrepreneurship. The surveys revealed that Winduaji possesses both human and natural resources conducive to coffee enterprise development, with market access through local coffee shops and tourism. Production training involved the procurement of equipment such as the MCP-250 pulper, FFC-I5 grinder, and a custom-built roasting tool. Packaging and branding were designed to increase product value, while marketing was conducted through participation in the EXPO UNSOED 2019. The results indicate improved technical literacy and entrepreneurial awareness among Pokdarwis members, along with initial validation of the local coffee product. These findings align with community-based entrepreneurship theory and similar service programs in other regions, emphasizing the importance of upstream-downstream integration and participatory approaches in rural economic empowerment.